Jamaica : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
Jamaica faced intense macroeconomic imbalances that threatened its macroeconomic stability. Executive Directors emphasized the need for credible policy actions and strong fiscal adjustment to reduce imbalances and lower vulnerability. They welcomed the strong fiscal adjustment in the budget and encouraged the Bank of Jamaica to reorient monetary policy. They stressed the need for a policy mix that would restore macroeconomic stability, achieve higher growth, lower external imbalances, and emphasized for anti-crime measures, infrastructure building, and sector-specific policies to promote growth.